Emotional State Can Affect Inflammatory Responses to Pain Among Rheumatoid Arthritis Patients: Preliminary Findings. Issue 6 (December 2019) - Graham-Engeland, Jennifer E.; Song, Sunmi; Mathur, Ambika; Wagstaff, David A.; Klein, Laura Cousino; Whetzel, Courtney; Ayoub, William T.
In a novel pilot study, we investigated how emotional state is related to inflammatory responses to acute pain among women with rheumatoid arthritis. Nine women completed four 5-hour visits that varied only by manipulation of emotion (anger, sadness, happiness, vs. control); in each visit, acute pain was elicited, with blood draws at baseline, 10 minutes, 60 minutes, and 100 minutes post-pain. We examined the effects of within-subjects factors on circulating inflammatory biomarkers interleukin (IL)-6, IL-10, tumor necrosis factor-α, C-reactive protein, and cortisol. There was a main effect of state anger on IL-6, with higher reported anger associated with higher IL-6 across conditions. Further, there were several interactions between state emotion and condition. For example, when individuals reported higher state anger in the sadness condition compared to their own average, they showed higher levels of IL-6 and cortisol. Findings are discussed within a larger literature suggesting that mixed emotional states can contribute to psychological stress and inflammatory responses.